THE AUTHENTIC LEADER (Fiep Bulletin - online, 2014)
The purpose of this article was to investigate the concept of leadership, explaining his methods, timing and situation where its precepts were formulated. From the nineteenth century the concept of the individual leader as a man born with this "gift" evolved into the current resolution of cooperation, given the fact that in everyday dealing with this power relationship between leader and follower. The methodology used was about leadership theories were refined with time and today are seen as tools that should fit the circumstances of the work being done by the group. That said there is a leader who can work with a recipe but to adapt to all factors given him as a raw material to make the proposto.Portanto work, the concept of Authentic Leader, is the most widely accepted today.
Keywords: Leadership; Authentic Leader; Moral Agent.